Kajian Biodegradasi Filem Plastik Campuran Polimer Sintetik dengan Biopolimer dalam Larutan Air - Octaviani, Melzi; Zaini, Erizal; Djamaan, Akmal (Indonesian Research Gateway)
The degradation of a plastic film containing polymer syntheticpolystyrene (PS) and biopolymer poly(3-hydroxybutyrate)[P(3HB)] and poly (3-hydroxybutyrate-co-3-hydroxy valerat)[P(3HB-co-3HV)] in various composition in aquous solution by in-vitro and in-vivo has been carried out. The testing was conducted based on immersion test in aquadest, river water, pH 4 solution, 6,8 and 10. Rate degradation measured use linear regression equality and parameter is time degradation 50% (t 50%), time degradation 95% (t 95%) and indicated by the slope (k). The result showed that, degradation of a plastic film containing PS and P(3HB) in pH 6 solution occurred faster, followed by ratio PS/P(3HB) 95:5, PS/P(3HB) 90:10, PS/P(3HB) 85:15 and PS/P (3HB) 80:20, in contrast degradation of pure PS (100:0) not occured. It is also observed that the biodegradation plastic film containing PS/P(3HB-co-3HV) in river water ratio PS/P(3HB-co-3HV) 95:5, PS/P (3HB-co-3HV) 90:10 and PS/P (3HB-co-3HV) 85:15, in contrast degradation of pure PS (100:0) not occurred.Keywords : biodegradation, polystyrene, poly(3-hydroxybutyrate), poly (3-hydroxybutyrate-co-3-hydroxyvalerat), plastic film.